HAKIKAT PERKEMBANGAN INDIVIDUAL DAN HUBUNGANNYA DENGAN PENDIDIKAN - Ainun, Nur; Dalimunthe, Rahmah Yasrah; Wahyuni, Sri (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this study is to find out the theory of student development. This type of research is library research. This research makes Library materials as its main data source. Student development is part of the study and application of developmental psychology which specifically studies aspects of individual development (students) starting from early childhood education, elementary school, SMP-SMA/SMK/MA. An educator or teacher who helps develop the potential of students is required to understand the behavior and changes in students and must be able to understand the growth and development that occurs in studentsEvery time a person's mindset must increase, along with the development of one's brain, the learning process is very important to support children's intelligence in the future. Student development is an important component that a teacher must know. A correct understanding of student development will lead teachers to make learning designs.